Synergistic Effects of Methotrexate and Suberoylanilide Hydroxamic Acid in Triggering Apoptosis of Chronic Myeloid Leukemia Cells - YALÇIN, AHMET SUHA; YILMAZ GÖLER, AYŞE MİNE (AKAD DOKTORLAR YAYINEVI, 2015)
In this study, we have investigated the effects of suberoylanilide hydroxamic acid (SAHA) against chronic myeloid leukemia (CML) cells in combination studies with methotrexate (MTX), which is a dihydrofolate reductase inhibitor used in combination therapy with other agents or alone. Combination of synergistic ratios of MTX and SAHA led to apoptotic cell death of CML cells via PARR cleavage, cytochrome c release and ROS increase in vitro. We suggest that combination of MD( and SAHA may minimize the toxicity and side effects of SAHA treatment, thus providing lower amounts of each drug in CML treatment.
Keywords: Chronic myeloid leukemia; Methotrexate; Suberoylanilide hydroxamic acid; Apoptosis; HISTONE DEACETYLASE INHIBITOR; ACUTE LYMPHOBLASTIC-LEUKEMIA; COMBINATION THERAPY; HDAC INHIBITORS; CANCER-THERAPY; EXPRESSION; ACETYLATION; GENE; SAHA; PROLIFERATION